Credit, investments, and the macroeconomy - Mazzoli, Marco (Cambridge University Press, 1998)
This book relates the literatures of finance, industrial economics and investment to the theoretical framework of the 'credit view'. Firstly it is assumed that banks' decisions concerning their assets are seen as at least as relevant as their decisions concerning their liabilities. Secondly, securities and bank credit are considered to be highly imperfect substitutes. In this regard it is important to investigate the way industrial and financial sectors interact. In particular, how is the macroeconomy affected by the phenomenon of 'securitization' and by exogenous changes in the industrial structure of the credit market. The interactions between real and financial sectors are also analysed from the point of view of the industrial firm, in a model where the investment and financial decisions of the firm are taken simultaneously
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Credit; Asset-liability management; Macroeconomics; Bilanzstrukturmanagement; Bank; Kreditmarkt; Industriebetrieb